Tindak Tutur Ilokusi pada Film “Naqah” Karya Meshal Al Jaser (Kajian Analisis Pragmatik Teori Searle): Illocutionary Speech Acts in the Film “Naqah” by Meshal Al Jaser (A Pragmatic Analysis Study of Searle's Theory) - Akbar Rizky Mahendra; Mugy Nugraha; Yani’ah Wardani; Ekawati Ekawati (Information Technology and Science(ITScience), 2026)
This study aims to analyze illocutionary speech acts in the film N?qah by Meshal Aljaser using pragmatic studies and John R. Searle's speech act theory. This study is a descriptive qualitative study with data in the form of dialogues in the film N?qah. The data collection techniques used are listening, documentation, and note-taking techniques. Data analysis is carried out through the process of identification, classification, and description based on the categories of speech acts proposed by Searle. The results of the study indicate that there are three types of illocutionary speech acts, namely assertive speech acts with four data, directive speech acts with five data, and expressive speech acts with two data. Assertive speech acts are used to convey information, opinions, and beliefs of the speaker. Directive speech acts are used to give orders, requests, prohibitions, and invitations. Meanwhile, expressive speech acts are used to express the feelings, attitudes, and emotional responses of the speaker. The findings of this study indicate that illocutionary speech acts have an important role in building interactions between characters, strengthening the communication context, and supporting the development of the storyline and character depiction in the film. This study also shows that pragmatic analysis of films can provide a deeper understanding of language functions, communication strategies, and the relationship between utterances, context, and speaker goals. This study enriches pragmatic research, particularly in the study of illocutionary speech acts.